Students’ Perspective on the Smoke-Free Campus Application at a University in Izmir - Babaoglu, Asya Banu; Timarci Becerik, Ilgin; Ucar, Melis (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: This study aimed to assess the level of knowledge among students regarding the smoke-free campus concept at a university in Izmir and evaluate their perspectives on its implementation. A cross-sectional study was conducted during the 2022–2023 academic year, involving 486 students at a university in Izmir. Participants completed an online questionnaire, which gathered data on their sociodemographic characteristics, smoking status, and their attitudes toward the smoke-free campus initiative. Among the participants, 50.6% were female, and the median age was 20 years. Approximately 35% of students were smokers. Notably, 55.1% of participants had never heard of the smoke-free campus concept. Non-smokers were significantly more likely to report being “exposed to passive smoking,” feeling “disturbed by it,” and acknowledging the health risks associated with passive smoking. Students who smoked exhibited lower support for switching to a smokefree campus,” perceiving it as “discriminatory practice.” Approximately 54.9% of students believed that “student participation in creating a smoke-free campus would impact its success,” and 91.8% agreed that “student opinions should be considered when determining smoke-free campus policies.” The study reveals an inadequate level of knowledge among students regarding the smoke-free campus concept, with a considerable portion being unaware of its existence.
Keywords: Smoke-free policy; tobacco; tobacco smoke pollution; tobacco use disorder; universities